Assimilation and catabolism of dispensable and indispensable free amino acids in post-larval Senegal sole (Solea senegalensis) - Rønnestad, I. (2014)
The postprandial metabolism of dietary free amino acids (AA) was studied in post-larval Senegal sole, Solea senegalensis, aged 32 days after hatching (DAH). The diet was administered as a single pulse (36 nl, 43.1 mmol/l) using a micro tube-feeding technique and a dissolved mixture of crystalline AA. In four separate treatments the diet contained L [U-14C] tracer for two indispensable AA (IAA), lysine and arginine or two dispensable amino acids (DAA), glutamate and alanine. The post-larva absorbed all tested AA from the diet with similar efficiency (97.5%). A small fraction of the IAA was catabolised (11.5±1.1 and 15.1±3.3%, for lysine and arginine, respectively) and a high proportion was retained in the body (86.7±1.3 and 81.6±4.1%). For the DAA more were catabolised (64.9±5.3% and 41.4±7.2% for glutamate and alanine, respectively) and less were retained (32.9±5.1% and 56.3±7.2%). On this basis, it appears that post-larval Senegal sole use DAA in preference to IAA as energy substrates while the retention (assimilation efficiency) is better for the IAA. These results support other recent studies that early stages of fish have a better capacity to regulate AA catabolism than previously believed and that indispensable AA are saved for body growth.